Inuit harvesting levels of caribou in the Kitikmeot Region, Northwest Territories, Canada, 1982 — 1984 - Jingfors, Kent (Rangifer, 1986)
Information on the native harvest of caribou (Rangifer tarandus spp.) has been systematically collected in the Kitikmeot (Central Arctic) Region of the Northwest Territories since October 1982 through a cooperative effort between the Kitikmeot Hunters and Trappers Association and the Department of Renewable Resources. During the first 2 years of the study about 640 active hunters in 7 communities, or 20% of the Inuit population, were included. Local fieldworkers contacted an average of 80% of all hunters each month. The estimated regional harvest between October 1982 and September 1984 was 18 827±260 (SE) caribou. In the reported harvest (n=12 969), bulls dominated (54%) followed by cows (32%) and juveniles (<15 months old; 14%). The successful hunters harvested on the average 3.5 caribou/hunter/month. When extrapolated over the total Inuit population in the Region, the estimated caribou harvest was equivalent to an annual harvest of 3.1 caribou/person. This harvest level was relatively consistent between communities and years.